Final Conference on „Social Inclusion and human Rights in macedonia“, Struga, macedonia - Team, Editorial (Ревија за социјална политика/Journal of Social Policy, 2013)
Тhe Ludwig Boltzmann Institute for Human Rights organized its final Conference within the framework of the project „Social Inclusion and Human Rights in Macedonia“ from 10 to 12 December, at the Hotel Drim in Struga. Conference participants revised the previously adopted local Strategies for social inclusion, social protection and poverty reduction 2011-2015 in partnering municipalities of Berovo, Pehcevo, Radovish, Konche, Negotino, Studenichani and Cashka. Participants included representatives of local self-government units, various institutions, citizen organizations and other relevant entities in the above municipalities which were previously involved in the strategy preparation process. Local action plans in the fields of: social inclusion, social protection and poverty reduction, were subject of revision.